2012
DOI: 10.1021/am301425e
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Oriented Iron Oxide Films Produced by Hydrothermal Process: Effect of Thermal Treatment on the Physical Chemical Properties

Abstract: Our study describes the influence of the thermal treatment on the fundamental properties of the vertical oriented iron oxide nanorods synthesized under hydrothermal condition onto a conductor substrate. X-ray diffraction and X-ray absorption near edge structure spectra were used to investigate the phase evolution from iron oxyhydroxide (β-FeOOH) to pure hematite phase. The formation of nanorods distributed along of substrate was observed by top-view SEM images and the rod growth preferentially oriented at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 83 publications
1
39
1
Order By: Relevance
“…Figure S24 (Supporting Information) shows the catalytic HER activity of FeSe 2 /NF and those of commercial IrO 2 /NF and Pt catalysts. A strong redox response was observed in the lower current density region for FeSe 2 /NF, indicating the reduction of Fe from mixed +2/+3 to a more reduced state akin to what is reported for FeO x ‐type materials . As a consequence of the interfering redox response in the region of lower current densities (−10 mA cm −2 ), the overpotentials were defined and compared at a current density of −100 mA cm −2 (Supporting Information, Table S10).…”
Section: Figurementioning
confidence: 80%
“…Figure S24 (Supporting Information) shows the catalytic HER activity of FeSe 2 /NF and those of commercial IrO 2 /NF and Pt catalysts. A strong redox response was observed in the lower current density region for FeSe 2 /NF, indicating the reduction of Fe from mixed +2/+3 to a more reduced state akin to what is reported for FeO x ‐type materials . As a consequence of the interfering redox response in the region of lower current densities (−10 mA cm −2 ), the overpotentials were defined and compared at a current density of −100 mA cm −2 (Supporting Information, Table S10).…”
Section: Figurementioning
confidence: 80%
“…[23] In particular, herein, ag ood linear fit (R 2 > 0.99) of the Mott-Schottky plots for all pure and tin-modified hematite waso bserved ( Figure S5 in the Supporting Information). Accordingt oE quation (6), the slope of the plots was inverselyp roportional to the donor charge density of the semiconductor film. The positive slopes indicatet hat pure and tin-modified hematite electrodes are ntype semiconductors.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the OER by CV,the TEM and HRTEM images revealed athin amorphous shell, which appeared to start growing on the surface of the particles,c onfirming immediate changes on the surface at applied potentials (Supporting Information, Figure S27), while the thickness of the amorphous shell was further increased after OER by CP ( Supporting Information, Figure S28). [19] Both HRTEM and the SAED pattern showed that the core of the particle was intact (Supporting Information, Figure S28). [19] Both HRTEM and the SAED pattern showed that the core of the particle was intact (Supporting Information, Figure S28).…”
Section: Zuschriftenmentioning
confidence: 99%
“…Theresulting overpotentials are not only one of the lowest in the series of chalcogenides,b ut also lower than that of most highperformance transition-metal-based catalysts (Supporting Information, Tables S7 and S8). [19] Scheme 1. [19] Scheme 1.…”
mentioning
confidence: 99%